Study of Factors Affecting the Dielectric Strength of [Ep/ZrO2 – y2O3] Nanocomposites - H.M. Alfalahi, Ahmad; ., . (International Journal of Engineering and Technology, 2018)
A nanocomposite material was prepared from epoxy resin reinforced by nanoceramic powder [Nano Zirconia – Yttria, (ZrO2 – y2O3) (70-80nm)], with several weight ratios (1.5, 2.5, 3.5, 4.5 Wt%), the research samples were prepared according to the standard specifications in different thicknesses (1, 1.5, 2, 2.5mm). The effect of addition rate (Wt%) was studied in addition to  the thickness, number of cycles, and average of voltage increase, on the dielectric strength (Ebr) for the composites before immersion, then, the effects of immersing the composite material in distilled water  were observed also in NaOH and HCL diluted solutions (0.5 N)  were observed .The test results revealed an increase in( Ebr) with increasing the addition of (ZrO2 – y2O3) [( from 27.8 kv/mm for a ratio of 1.5 Wt% to 33.4 kv/mm for a ratio of 4.5Wt% at the average of voltage increase 0.5 kv/s) (and from 31.4 kv/mm for a ratio of 1.5Wt% to 36.7 kv/mm for a ratio of 4.5Wt% at the average of voltage increase of 5kv/s)], and with increasing average voltage increase, on the contrary,( Ebr) decreases with increasing the sample thickness, number of cycles, and immersion in distilled water and chemical solutions (with immersion period) noticing that the chemical solutions effect was greater than that of the distilled water.